One more rep! The case for resistance training in young cancer survivors - Lakicevic, Nemanja; Ficarra, Salvatore; Ortega-Gómez, Sonia; Jiménez-Pavón, David; Asimakopoulou, Zoi; Vantarakis, Apostolos; Tavares, Paula; Vaz, Vasco; Thaller, Joshua; Papakonstantinou, Sofia; Kirkar, Musa; Glorioso, Francesca; et al. (Frontiers in Oncology, 2023)
Resistance training is now seen as a powerful tool to improve health and functionality of cancer survivors. Literature shows that it can be implemented both during and after cancer treatment, with the intent of preserving muscle mass in the former and increase muscle mass in the latter case. However, currently available data on this matter is predominantly derived from adult cancer survivors (ACS) and it is questionable whether the exact same training regimen should be implemented in young cancer survivors (YCS) given the unique challenges they experience throughout their disease trajectory. Therefore, the goal of this work is to distil the existing evidence on RT interventions in ACS and facilitate discussion on whether the same patterns of RT can be applied in YCS.